The Functions of DNA Damage Factor RNF8 in the Pathogenesis and Progression of Cancer - Zhou, Tingting (Int J Biol Sci, 2019)
The really interesting new gene (RING) finger protein 8 (RNF8) is a central factor in DNA double strand break (DSB) signal transduction. DSB damage is the most toxic type of DNA damage to cells and is related to genomic instability. Multiple roles for RNF8 have been identified in DNA damage response as well as in other functions, such as telomere protection, cell cycle control and transcriptional regulation. These functions are closely correlated to tumorigenesis and cancer progression. Indeed, deficiency of RNF8 caused spontaneous tumorigenesis in a mouse model. Deciphering these mechanisms of RNF8 may shed light on strategies for cancer treatment. In this review, we summarize the current understanding of both classical and nonclassical functions of RNF8, and discuss its roles in the pathogenesis and progression of tumor.